PERAN GURU PENDIDIKAN AGAMA ISLAM SEBAGAI FASILITATOR DALAM PENINGKATAN KEDISIPLINAN SISWA - Qonita Setyaningsih; Joko Subando (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
The teacher as the subject, has a role in the formation of disciplinary character. PAI teachers who always teach by giving advice and motivation, do not forget to also reprimand and give educational punishments to students who break the rules. The use of existing learning methods and media is also maximized in conveying PAI material in class and training children's discipline, such as the question and answer method, discussion and group work. Apart from that, the core material of PAI can also be found in school activities such as Duha prayers, the habit of ablution and praying on time. Then in an effort there must be supporting and inhibiting factors. Likewise at SMP Negeri 6 Surakarta. In practice teachers, parents, peers and the community environment can be factors that support or hinder efforts to build this disciplinary character.